Animal Rights/Human Rights: Entanglements of Oppression and Liberation - Nibert, David (Rowman & Littlefield Publishers, 2002)
This accessible and cutting-edge work offers a new look at the history of western 'civilization,' one that brings into focus the interrelated suffering of oppressed humans and other animals. Nibert argues persuasively that throughout history the exploitation of other animals has gone hand in hand with the oppression of women, people of color, and other oppressed groups. He maintains that the oppression both of humans and of other species of animals is inextricably tangled within the structure of social arrangements. Nibert asserts that human use and mistreatment of other animals are not natural and do little to further the human condition. Nibert's analysis emphasizes the economic and elite-driven character of prejudice, discrimination, and institutionalized repression of humans and other animals. His examination of the economic entanglements of the oppression of human and other animals is supplemented with an analysis of ideological forces and the use of state power in this sociological expose of the grotesque uses of the oppressed, past and present. Nibert suggests that the liberation of devalued groups of humans is unlikely in a world that uses other animals as fodder for the continual growth and expansion of transnational corporations and, conversely, that animal liberation cannot take place when humans continue to be exploited and oppressed.